Mental Health Literacy, Access, and Service Utilization in Indonesia: A Study of Public and Psychologists' Perspectives - Farhan Zakariyya; Alwin Muhammad Reza; Rini Maulida; Muhammad Ilham Mudin (Universitas Ahmad Dahlan, 2026)
Mental health disorders are a major public health challenge in Indonesia, yet overall services are underutilized. We surveyed 360 community members and 65 licensed psychologists to examine mental health literacy, access, and service utilization. Descriptive statistics and ANOVA tested demographic differences in three literacy dimensions: general awareness, treatment attitudes, and self-readiness. Under hypothetical norms, 97.5% met “high” awareness, but only 73.1% did so empirically; 66.4% showed moderate overall literacy, revealing persistent gaps between expected and observed performance. Literacy was higher among females (d = 0.576), postgraduates versus high school graduates (10.8%, η² = 0.034), and psychology versus business students (η² = 0.099). Personal or family exposure to mental health problems predicted higher literacy (d = 0.259–0.517). Access was rated moderate by 69.4%. Psychologists highlighted client-related difficulties, administrative burden, and skill limitations. Both groups cited cost, stigma, low awareness, and logistical barriers, indicating the need for coordinated individual- and system-level interventions.